PENGETAHUAN LANJUT USIA TENTANG HIPERTENSI DI WILAYAH KERJA PUSKESMAS WENANG KOTA MANADO - Kristamuliana; Valen Fridolin Simak; Septriani Renteng (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2022)
Increased blood pressure is a condition that is often experienced by the elderly. This condition can be caused by age related factors and risk factors. One of the risk factors for increasing blood pressure in the elderly is a lack of knowledge about blood pressure. The purpose of this study was to determine the description of knowledge of Elderly about hypertension in the Wenang Health Center Work Area, Manado City. The research design used is descriptive research with survey method, and the number of samples are 76 elderlies. The sampling technique used was institutional based accidental sampling, in which researchers took samples that happened to meet at institutions (Puskesmas and Posyandu). The instrument used is HK-LS (Hypertension Knowledge Level Scale). The results showed that the elderly in the working area of ​​the Wenang Health Center Manado City had knowledge of hypertension at a good level of 28.9% and at a low level of 71.1%. This is because the level of education is mostly at a low level of 63.2% and also patients with hypertension grade I and II who are believed to have good experience on all matters related to hypertension only 32.9%. The conclusion of this study is that the knowledge of the elderly at the Manado City Health Center regarding hypertension is mostly still at the low level of knowledge.